Association between fetal fraction on cell‐free DNA testing and first‐trimester markers for pre‐eclampsia. (26th October 2018) - Rolnik, D. L.; da Silva Costa, F.; Lee, T. J.; Schmid, M.; McLennan, A. C.
ABSTRACT: Objectives: To evaluate the association between fetal fraction on cell‐free DNA (cfDNA) testing and first‐trimester markers for pre‐eclampsia, and to investigate the possible association of low fetal fraction with increased risks for pre‐eclampsia (PE) and fetal growth restriction (FGR). Methods: This was a retrospective cohort study including all women with a singleton pregnancy who had risk calculation for PE and FGR between 11 + 0 and 13 + 6 weeks' gestation and who also had cfDNA as a primary or secondary screening test for chromosomal abnormalities at any gestational age at two fetal medicine clinics in Sydney and Melbourne, Australia, between March 2013 and May 2017. Logarithmically transformed fetal fraction results were adjusted for gestational age and maternal characteristics. Associations with mean arterial pressure (MAP), mean uterine artery pulsatility index (UtA‐PI), pregnancy‐associated plasma protein A (PAPP‐A), placental growth factor (PlGF), and risks for PE < 34 weeks, PE < 37 weeks and FGR < 37 weeks were analyzed using correlation analysis and univariable and multivariable linear regressions. Results: In total, 4317 singleton pregnancies that underwent cfDNA testing with fetal fraction reported were included. Significant prediction of fetal fraction was provided by gestational age, conception by in‐vitro fertilization, maternal age, body mass index, chronic hypertension, diabetes mellitus, South Asian ethnicity and being parous without history of PE or FGR. Fetal fraction was associated inversely with MAP and UtA‐PI and associated positively with PAPP‐A and PlGF. The lower the fetal fraction, the higher were the risks for PE < 34 weeks, PE < 37 weeks and FGR < 37 weeks ( P  < 0.001 for all). Conclusions: There is a significant association between fetal fraction result and first‐trimester markers for adverse pregnancy outcome. Low fetal fraction is associated with an increased risk for pregnancy complication, but its capacity to act an as independent first‐trimester marker in an algorithm for screening for PE and FGR requires further research. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.